Kajian Potensi dan Nilai Ekonomi Sumber Daya Perikanan Tangkap Danau Hanjalutung Kota Palangka Raya - Maryani, Maryani; Chusnul Chatimah, Hastin Ernawati Nur; Saraswati, Dewi; Kusumadati, Wijantri; Aziz, Fadhila; Nugrahayu, Hera; Toana, Ahmad Averus; Irawan, Heri; Rahman, Fauzi; Utama, Kurniawan S. (Jurnal Akuakultur Sungai dan Danau, 2025)
Hanjalutung Lake in Palangka Raya City holds significant potential for capture fisheries that support food security and the local economy. The diversity of native fish such as baung (Hemibagrus nemurus), lais (Kryptopterus spp.), saluang (Rasbora spp.), and sepat (Trichogaster spp.) provides the main source of income for traditional fishers. The study indicates that resource utilization remains within a safe limit (fMSY ± 274 fishing days/year), although a declining trend in Catch Per Unit Effort (CPUE) suggests increasing pressure on fish stocks and the lake ecosystem. From the socio-economic perspective, fishers face limited access to capital, weak institutional support, and low diversification of livelihoods, coupled with inadequate post-harvest infrastructure. Nevertheless, there are significant opportunities for development through product diversification, particularly high-value fish-based products such as shredded baung, saluang chips, and smoked lais. These products have broad market potential and could strengthen the culinary identity of the region. The recommended management strategies include strengthening ecological data as the basis for policy, enhancing fisher capacity, improving post-harvest infrastructure, and integrating fisheries with ecotourism through fish harvest festivals and traditional fishing attractions. With inclusive and evidence-based governance, Hanjalutung Lake has the potential to be developed as a sustainable hub for creative economy and ecotourism in Palangka Raya City.